Role of tannic acid against SARS-cov-2 cell entry by targeting the interface region between S-protein-RBD and human ACE2 - Chen, Xi; Wang, Ziyuan; Wang, Jing; Yao, Yifan; Wang, Qian; Huang, Jiahao; Xiang, Xianping; Zhou, Yifan; Xue, Yintong; Li, Yan; Gao, Xiang; Wang, Lijun; et al. (Frontiers in Pharmacology, 2022)
The outbreak of coronavirus disease 2019 (COVID-19) was caused by a novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). To gain entry into cells, SARS-CoV-2 takes advantage of human angiotensin converting enzyme 2 (hACE2) as cellular receptor of its spike glycoprotein (SP). Thus, we focused on the potential of repurposing the clinically available drugs to block the binding of SARS-CoV-2 to hACE2 by utilizing a novel artificial-intelligence drug screening approach. The pharmacophore of SARS-CoV-2-receptor-binding-domain (S-RBD) -hACE2 interface was generated based on the structure of S-RBD and hACE2, which was used as a query to screen a library of FDA-approved drugs. A total of 20 drugs were retrieved as S-RBD-hACE2 inhibitors, in which 16 drugs were identified to bind to S-RBD or hACE2. Notably, tannic acid was validated to interfere with the binding of S-RBD to hACE2, thereby inhibited pseudotyped SARS-CoV-2 entry. Competitive inhibition experiments revealed that tannic acid competes with S-RBD and hACE2 while molecular docking proved that tannic acid interacting with the essential residues of RBD and hACE2. Based on the known antiviral activity and our results, tannic acid may serve as a promising candidate for the prevention and treatment of SARS-CoV-2 infection.